The empowered manager positive political skills at work - Block, Peter 1939- (Ascent Audio, 2024)
Empowerment produces the conditions for high performance. Especially for middle managers and below. Empowered cultures attract and retain talent. They produce high achievement, high accountability, and high commitment. Bestselling author Peter Block is a true visionary: author of the classic Flawless Consulting, his work is about empowerment, stewardship, chosen accountability, and reconciliation of community. In The Empowered Manager, he returns his eye toward management to renew our efforts to create a shift in the traditional hierarchy. Twenty years after the original book, Block talks of why it is so difficult to both open the door to empowerment and more importantly, have people walk through it. It is more important than ever to create a culture in which all members of an organization are treated as entrepreneurs, giving them ownership over their role and responsibilities. This is in the face of the reality that most employees want safety, not the adventure of empowerment. If you feel controlled by bureaucracy, unrewarded for creativity, and powerless to control your own destiny, this book is the breath of fresh air your career has been craving. Timeless tips from a master of business strategy alongside a framework for more effective management makes The Empowered Manager a must-listen guide for anyone doing business today.
Online resource; title from title details screen (O'Reilly, viewed September 10, 2024)
Keywords: Organizational behavior; Organizational effectiveness; Office politics; Executive ability; Comportement organisationnel; Efficacité organisationnelle; Politique d'entreprise; Aptitude pour la direction; Audiobooks; Livres audio